Identification and characterization of dwarf cattle available in Dinajpur district (Asian Journal of Medical and Biological Research, 2016)
The present study was undertaken from January to June, 2014 to investigate the morphometric, productive and reproductive characteristics of Dwarf cattle available in Dinajpur District. The data obtained from 200 Dwarf cattle of different categories (yearling bull, adult bull, heifer, cow, male calf and female calf). A wide variety of coat colors among the cattle of the selected areas were found. The head length and width, ear length and width, horn length and diameter, neck length and width, body length at shoulder, wither height, heart girth, fore leg and hind leg length, tail length and diameter, teat length and diameter, distance between fore teats and rear teats, length and width of testis, weight of testis, live weight, daily milk yield, lactation length, gestation length, calving interval, dry period, post partum heat period, age at first heat and service per conception were recorded. The Dwarf cattle in Dinajpur District are comparatively smaller in size than most of the recognized breeds or types of cattle, however coat color showed remarkable variation. The data generated for Dwarf cattle in Dinajpur District would be useful to characterize them.Asian J. Med. Biol. Res. December 2015, 1(3): 380-386